Expanding Maize Genetic Resources with Predomestication Alleles: Maize–Teosinte Introgression Populations. Issue 1 (1st March 2016) - Liu, Zhengbin; Cook, Jason; Melia‐Hancock, Susan; Guill, Katherine; Bottoms, Christopher; Garcia, Arturo; Ott, Oliver; Nelson, Rebecca; Recker, Jill; Balint‐Kurti, Peter; Larsson, Sara; Lepak, Nicholas; et al.
Abstract : Teosinte ( Zea mays subsp. parviglumis H. H. Iltis & Doebley) has greater genetic diversity than maize inbreds and landraces ( Z. mays subsp. mays ). There are, however, limited genetic resources to efficiently evaluate and tap this diversity. To broaden resources for genetic diversity studies in maize, we developed and evaluated 928 near‐isogenic introgression lines (NILs) from 10 teosinte accessions in the B73 background. Joint linkage analysis of the 10 introgression populations identified several large‐effect quantitative trait loci (QTL) for days to anthesis (DTA), kernel row number (KRN), and 50‐kernel weight (Wt50k). Our results confirm prior reports of kernel domestication loci and identify previously uncharacterized QTL with a range of allelic effects enabling future research into the genetic basis of these traits. Additionally, we used a targeted set of NILs to validate the effects of a KRN QTL located on chromosome 2. These introgression populations offer novel tools for QTL discovery and validation as well as a platform for initiating fine mapping.